2017
DOI: 10.1017/s0950268817000619
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation ofSalmonellastrains isolated from outbreaks and sporadic cases of diarrhoea occurred in Paraná State, South of Brazil

Abstract: A total of 46 strains of Salmonella isolated from patients with sporadic diarrhoea or involved in foodborne outbreaks were analysed by PCR for genus identification and serotyping. Subtyping was performed using pulsed-field gel electrophoresis (PFGE) and multiple amplification of phage locus typing (MAPLT) for seven variable loci. Bacteria were identified as belonging to serotype Enteritidis (33 strains; 71·7%) or Typhimurium (13 strains; 28·3%). A high similarity coefficient (94·6%) was observed in the Salmone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This scenario is quite different from the main studies in Europe and North America where most isolates are from enteric origin. 30 , 31 Even the previous studies in South America have not demonstrated a so high frequency of non-enteric isolates. 28 On oppose, the rates of non-enteric and invasive salmonellosis are larger in Africa than in any other continent.…”
Section: Discussionmentioning
confidence: 97%
“…This scenario is quite different from the main studies in Europe and North America where most isolates are from enteric origin. 30 , 31 Even the previous studies in South America have not demonstrated a so high frequency of non-enteric isolates. 28 On oppose, the rates of non-enteric and invasive salmonellosis are larger in Africa than in any other continent.…”
Section: Discussionmentioning
confidence: 97%
“…To reduce the impact of outbreaks caused by foodborne pathogens, timely subtyping of isolates to incriminate sources of contamination is crucial. Conventional Salmonella typing methods such as PFGE, phage typing (PT), MLVA, and multiple amplification of phage locus typing (MAPLT) do not always provide the required level of discrimination (Assis et al, 2017 ; Ziebell et al, 2017 ). It was proposed previously that prophage composition could differentiate between S .…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Salmonella enterica has been reported as the main isolated pathogen in foodborne outbreaks and S. Typhimurium has been pointed as the first or second most isolated serovar in the country, depending on the location [6][7][8].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%